Industrial Food for Thought: Timescapes of Risk. (1st May 1999) - Adam, B.
Abstract : This paper explores the temporal dimension of risks associated with the production, trade and consumption of food. The paper operates at many levels of substantive and theoretical analysis: it focuses on problems for understanding and action that arise from the invisibility of the hazards, explores the effects of those hazards on consumers and sets out the differences in risks that are faced by farmers, processors, traders and consumers. With its emphasis on that which tends to be disattended in conventional social science analysis - the temporal and the invisible - the paper has implications for social theory at the level of ontology and epistemology. It concludes with reflections on the role of social theory in such contemporary timescapes of risk.